Guarantee, Promotion and Ideas of Omnibus Law on Health in Indonesia Compared to Singapore and Taiwan - Sudaryat, Sudaryat (Universitas Semarang, 2024)
This study aims to compare and analyze macro health policies in Indonesia with those in Taiwan and Singapore. The results of the comparison and analysis will be used as lessons learned and input for improving health policies in Indonesia in the future. Health policies in the form of the BPJS Kesehatan program have not optimally improved the health of the Indonesian people in terms of services, medicines, medical personnel, and health facilities. Taiwan is the country with the most superior health services in the world in 2024 and Singapore is the country with the best health system in the world in 2023. Through a normative legal research method with qualitative legal data analysis, it is known that the health policies implemented by the Taiwanese and Indonesian governments are almost the same, namely using an insurance mechanism with contributions from participants, the government and the private sector, but the differences in the reach and standardization of health services in Taiwan are wider in scope compared to Indonesia, while the Singaporean government in its health policy implements four programs, namely medisave, medishield, medifund, eldershield with control over increasing health financing from the government. Health policies in Taiwan are easier for the Indonesian government to apply in perfecting the BPJS Kesehatan program than those implemented by Singapore because both have implemented health policies through mandatory insurance programs. BPJS Kesehatan must improve its service management and the government needs to increase the number of health facilities and standardization of health facilities by adjusting its characteristics as an archipelagic country. Formulate fair premi for participants so that participants get optimal health services. Health promotion must be encouraged to increase public health awareness. The health omnibus law as a national legal strategy can be used as a trigger to harmonize overlapping health policies so that health programs can be implemented optimally which has an impact on improving the health of the Indonesian people.